2004
DOI: 10.1007/s00441-003-0842-x
|View full text |Cite
|
Sign up to set email alerts
|

Cytoskeletal filaments and associated proteins during restricted trophoblast invasion in bovine placentomes: light and transmission electron microscopy and RT-PCR

Abstract: Trophoblast cell migration is unusual in epitheliochorial placentae but occurs in placentomes of cows as "restricted" trophoblast invasion of binucleated trophoblast giant cells (TGC). Migration may be induced by integrin binding to the extracellular matrix initiating two pathways: (1) conformational changes of the actin cytoskeleton induced by an accumulation of its associated proteins and (2) integrin-dependent phosphorylation of various protein kinases. In cow placentomes, actin, its associated proteins (al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 50 publications
1
4
0
2
Order By: Relevance
“…This in vitro observation correlated with observations in vivo where ACTN expression was localized to the apicolateral compartment of the caruncular epithelial cells. Similar localization of ACTN was previously reported for the bovine placentome via electron microscopy with the immunoperoxidase/diaminobenzidine staining [32]. Further, apical ACTN linking to b-integrin subunits as a response to SPP1 (osteopontin)-mediated trophoblast-endometrial signaling in the ovine and porcine endometrial epithelium and cultured epithelial and trophectodermal cells has been demonstrated [22,23].…”
Section: Focal Adhesions Assemble Between Caruncular Epithelial Cellssupporting
confidence: 65%
“…This in vitro observation correlated with observations in vivo where ACTN expression was localized to the apicolateral compartment of the caruncular epithelial cells. Similar localization of ACTN was previously reported for the bovine placentome via electron microscopy with the immunoperoxidase/diaminobenzidine staining [32]. Further, apical ACTN linking to b-integrin subunits as a response to SPP1 (osteopontin)-mediated trophoblast-endometrial signaling in the ovine and porcine endometrial epithelium and cultured epithelial and trophectodermal cells has been demonstrated [22,23].…”
Section: Focal Adhesions Assemble Between Caruncular Epithelial Cellssupporting
confidence: 65%
“…All these cytoskeletal components have been localized before to define cell types within placental tissues of the cow [Lang et al, 2004;Pfarrer, 2005].…”
Section: Establishment Of a Cell Culture Model Of Bovine Placental Cementioning
confidence: 99%
“…Based on the ultrastructural appearance and the fact that actin is a main component of the microvilli frame in other epithelial cells [Fath and Burgess, 1995;Coch and Leube, 2016], we interpret this electron-dense material in both cell types as a part of the actin cytoskeleton. This interpretation is reinforced by immunogold [Lang et al, 2004] and immunohistochemical staining [Nakano et al, 2005]. Actin [Lang et al, 2004] as well as α 6 -and β 1 -integrin subunits and laminin [Pfarrer et al, 2003] have been suggested to be involved in TGC migration.…”
Section: Discussionmentioning
confidence: 86%
“…This interpretation is reinforced by immunogold [Lang et al, 2004] and immunohistochemical staining [Nakano et al, 2005]. Actin [Lang et al, 2004] as well as α 6 -and β 1 -integrin subunits and laminin [Pfarrer et al, 2003] have been suggested to be involved in TGC migration. As α 6 β 1 -integrin, also called VLA-6 (very late antigen-6) [Hemler et al, 1988], can interact indirectly with actin intracellularly [Alberts et al, 2015] and with laminin extracellularly Alberts et al, 2015], the simultaneous staining of laminin and α 6 -and β 1 -integrin subunits along the cell membrane of TGCs lead to the interpretation that these proteins cooperate in TGC migration [Pfarrer et al, 2003].…”
Section: Discussionmentioning
confidence: 86%